Approach and Communication in Learning - Azzahra, Fatimah; Sriwardona, Sriwardona; Safitri, Zahra (Ahlussunnah: Journal of Islamic Education, 2025)
This study discusses approaches and communication in learning as two crucial aspects that influence the effectiveness of the educational process. Using library research, this study reviews various current literature, books, and journals that discuss the theory and practice of learning approaches and communication. The main focus of this study is to understand how appropriate learning approaches can support effective communication processes between teachers and students, thus creating productive and meaningful learning interactions. The results of the study indicate that adaptive and communicative learning approaches are crucial in increasing student engagement and understanding. Furthermore, clear, open, and interactive communication is also a determining factor for successful learning. Communication barriers that arise can be minimized through the implementation of appropriate communication strategies by teachers. This study provides a theoretical contribution to the development of learning models oriented towards interaction and effective communication in today's educational context.